2015
DOI: 10.1186/s12864-015-1230-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrating transcriptomics and proteomics to show that tanshinone IIA suppresses cell growth by blocking glucose metabolism in gastric cancer cells

Abstract: BackgroundTanshinone IIA (TIIA) is a diterpene quinone extracted from the plant Danshen (Salvia miltiorrhiza) used in traditional Chinese herbal medicine. It has been reported to have anti-tumor potential against several kinds of cancer, including gastric cancer. In most solid tumors, a metabolic switch to glucose is a hallmark of cancer cells, which do this to provide nutrients for cell proliferation. However, the mechanism associated with glucose metabolism by which TIIA acts on gastric cancer cells remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 71 publications
(80 reference statements)
4
46
0
Order By: Relevance
“…In this study, we found that TSIIA decreased significantly the cell viability of EESCs in a dose-dependent manner, and 20 lL of TSIIA could result in obviously decreased cell viability; this is similar to recent observations that TSIIA could inhibit multiple cancer cells proliferation [20,36,37]. Furthermore, overexpression of 14-3-3f could restore cell viability of TSIIA-treated EESCs, implying that the inhibitory effect of cell viability was mediated by 14-3-3f.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we found that TSIIA decreased significantly the cell viability of EESCs in a dose-dependent manner, and 20 lL of TSIIA could result in obviously decreased cell viability; this is similar to recent observations that TSIIA could inhibit multiple cancer cells proliferation [20,36,37]. Furthermore, overexpression of 14-3-3f could restore cell viability of TSIIA-treated EESCs, implying that the inhibitory effect of cell viability was mediated by 14-3-3f.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, multiple studies have shown that TSIIA has therapeutic effects on different types of cancers, exhibiting with decreased cell viability, increased cell apoptosis, inhibition of cell invasion and migration [19,20]. The potential therapeutic mechanisms might be versatile, including inhibition of DNA synthesis and increased cell apoptosis [19,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cancer systems biology approach is very effective in identifying drug targets, developing novel therapeutics and new indications for existing drugs. [7][8][9][10] In addition to target and drug discovery, cancer systems biology represents a valuable contribution to efforts toward understanding the molecular mechanism of drugs in various cancer types 5,11 and regulation in cancer progression. 4 …”
Section: Systems Biology In Cancer Researchmentioning
confidence: 99%
“…For example, tanshinone IIA (TIIA) is a diterpene quinone extracted from the plant Danshen (Salvia miltiorrhiza), which is used in traditional Chinese medicine. 11,25 By analyzing RNA-sequencing and proteome data in TIIA-treated gastric cancer cells, TIIA was found to suppress cell growth by blocking glucose metabolism. 11…”
Section: Proteomes For Molecular Regulation Studiesmentioning
confidence: 99%